Combination of SHS and Mechanochemical Synthesis for Nanopowder Technologies - T. Grigorieva; M. Korchagin; N. Lyakhov (KONA Powder and Particle Journal, 2014)
The combination of mechanochemical activation and self-propagating high-temperature synthesis (SHS) have widened the possibilities for both methods. For metallic systems, the investigation showed that a short-term mechanochemical activation of heterophase SHS products leads to single-phase and ultrafine intermetallides obtained from the elements by mechanical alloying. It was demonstrated that metastable phases, usually obtained by mechanical alloying, can be obtained from the equilibrium intermetallic compounds synthesized by SHS. Besides this, the investigations showed that preliminary mechanical activation, during which layered composites are formed from the initial elements, allows one to extend the concentration limits of SHS processes up to a solid solution region.The preliminary mechanical activation also allows production of single-phase ultrafine complex oxides.